1. A.P
2. G.P
3. H.P
4. none
G.P
1. Y2 = 4 (a2 + a) (x – a)
2. Y2 = 4 (a’- a) (x –a )
3. Y2= (a’ + a)(x + a)
4. Y2 = 4 (a’- a) (x – a)
Y2 = 4 (a’- a) (x – a)
1. 1
2. -2
3. 2
4. none
-2
1. 5y2 + 2x – 21y + 20 = 0
2. 15y2 + 12x – 11y + 10 = 0
3. 18y2 – 12x + 21y + 56 = 0
4. 25y2 – 2x -65y + 120 = 0
5y2 + 2x – 21y + 20 = 0
1. X2 -4x -2y + 10 = 0
2. X2 – 2x –y +5 = 0
3. X2 - 4x – 2y + 10 = 0
4. Y2 – 2x – 3y + 4 = 0
X2 -4x -2y + 10 = 0
1. -1
2. -2
3. -3
4. -4
-4
1. b2-252=4ac
2. b3-5a2=4ac
3. b2+15a2=4ac
4. none
b2-252=4ac
1. nπ +π/3: n ε Z
2. nπ + tan-1(1/2): n ε Z or nπ+π/4: n ε Z
3. nπ + (-1)nπ/6: n ε Z
4. nπ + tan-1(3/2): n εZ or nπ+ tan-1(1/4): n ε Z
nπ + tan-1(1/2): n ε Z or nπ+π/4: n ε Z
1. a(a+2b)=c2
2. a(a+2c)=b2
3. b(b+2c)=a2
4. b(b+2a)=c2
a(a+2c)=b2
1. 12/25
2. -12/25
3. -24/25
4. 4/5
-24/25